PROBLEMATIKA PENGAWASAN PEMUTAKHIRAN DATA DAN PENYUSUNAN DAFTAR PEMILIH TAMBAHAN (DPTB) DAN DAFTAR PEMILIH KHUSUS (DPK) PADA PEMILU TAHUN 2024 - Huda, Uu Nurul (Jurnal Keadilan Pemilu, 2023)
Elections in Indonesia have a significant impact on state representation and policy. Election integrity and data updating, especially the Additional Voter List (DPTb) and Special Voter List (DPK), are key to achieving inclusivity and overcoming voter change. This research emphasizes transparency and accountability in monitoring data updates, with a focus on a fair and open process. Involving a qualitative approach, literature studies, regulatory analysis, technical guidelines, and previous general election reports, the research aims to gain a holistic and in-depth understanding of the data updating process and preparation of the DPTb and DPK. Based on research results, guaranteeing citizens' voting rights involves a minimum age requirement of 17 years, not having their voting rights revoked by a court, and proof of residency. Related regulations, such as General Election Supervisory Agency Number 4 of 2023, regulate supervision by Bawaslu and Panwaslu. Organizing elections by the KPU requires responsibility for voter data with the principles of accountability, transparency and supervision, supported by technology, community participation and stakeholder collaboration to maintain the integrity of the election process and increase public trust.